Determinants of environmental behaviour among senior high school students in Bogor City: A multidimensional analysis of environmental literacy components - Wulan Sukma Yuliantisna; Nengsih Juanengsih; Eva Fadilah (EDUSAINS, 2026)
Environmental degradation requires not only technological solutions, but also environmentally responsible behavior shaped through education. This study examines the influence of environmental literacy components—knowledge, skills, and character—on environmental behavior among senior high school students in Bogor City. The researchers used a quantitative correlational design with 167 eleventh-grade students selected through purposive sampling. Data was collected using 9 multiple-choice items for environmental knowledge, 8 items for environmental skills, and Likert-scale questionnaires consisting of 8 items for environmental character and 12 items for environmental behavior. Data was analyzed using descriptive statistics, Pearson correlation, and multiple linear regression. The results show that students’ environmental literacy is moderate across all domains. Correlation analysis indicates weak relationships between cognitive components and environmental behavior, while behavior shows the strongest correlation with overall environmental literacy (r = 0,745). However, regression analysis reveals that knowledge, skills, and character do not significantly predict environmental behavior, either individually or simultaneously (R² = 0,029, p > 0,05). These findings indicate a gap between cognitive understanding and actual environmental action. The study concludes that cognitive and affective components do not solely determine environmental behavior, and that more complex mechanisms involving contextual, motivational, and experiential factors influence it. Therefore, environmental education should integrate cognitive learning with affective development and experiential learning to bridge the gap between understanding and behavior and to promote sustainable environmental action among students.